[PP.34.03] CIRCADIAN BLOOD PRESSURE PROFILE AND SLEEP APNEA. (September 2016) - Rozanska, M.; Talarowska, P.; Segiet, A.; Mozenska, O.; Kosior, D.A.
Abstract : Objective: While asleep, blood pressure (BP) and heart rate (HR) decrease by approximately 25% from average waking values. The consequent lowering of cardiac load and oxygen demand is substantial for proper cardiac function. Hypertension (HTN) is one of the most common comorbidity in patients with sleep apnea. Detailed data regarding circadian BP profile (CBPP) and sleep apnea are lacking. The aim of the study was to characterize the relationship between CBPP and different aspects of sleep apnea. Design and method: We retrospectively analyzed 1270 patients, treated in our outpatient sleep apnea clinic. All patients underwent polysomnography. Among 795 patients with diagnosed HTN, 83 patients with detailed data regarding CBPP obtained from 24-hours arterial BP monitoring were further analysed. We defined dippers as a 10–20% fall in nocturnal BP, non-dippers as less than 10% and reverse-dippers as 0% at most fall in nocturnal BP. Local ethics committee gave consent to conduct the study. Results: In our study population (795 patients) mean age was 60.1 ± 11.4 years, 69.4% were male, 64.9% were smokers, 63% were obese, 65% had hyperlipidemia, 59.9% reported snoring, 83.4% had additional diagnosis of OSA (average supine AHI 46.8 ± 35.2). Patients with OSA were statistically significantly older (p = 0.033), were more frequently male (p < 0.001), obese (p < 0.001) and more often had hyperlipidemia (p < 0.001). In the 83 patients subgroup we further analyzed there were 36, 1% dippers, 51, 8% non-dippers and 12, 0% reverse-dippers. Those groups did not differ in respect of patients' general characteristics and in respect of clinical features of sleep apnea. We found statistically significant: negative correlations (δ-Spearman's rank correlation coefficient) between average systolic BP during awake hours and mean duration of obstructive apneas, mixed apneas and hypopneas (δ1 = −0.282, δ2 = −0.222, δ3 = −0.237; p1 = 0.012, p2 = 0.049 and p3 = 0.036, respectively), positive correlation between average systolic BP during sleeping hours and supine AHI (δ = 0.252; p = 0.024) and positive correlation between average systolic BP during sleeping hours and oxygen distribution on desaturation index/hour (δ = 0.222; p = 0.049). Conclusions: We found significant correlations between different measures of CBPP and different measures of sleep apnea. Further studies on larger patients' cohorts are needed to assess the importance of those findings.